2014
DOI: 10.1097/01.dss.0000452627.91586.cc
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Cryosurgery Combined With Topical Silicone Gel Sheeting for the Treatment of Refractory Keloids

Abstract: The results of this study support the use of combined intralesional cryosurgery followed by the application of silicone gel sheeting to treat refractory keloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
15
0
3
Order By: Relevance
“…Furthermore, the long duration of freezing enhances the biochemical changes and the growth of ice crystals, increasing the rate of cell death. 26 It has been reported that power of up to [35][36][37][38][39][40] W is required to destroy cancerous cells and that two freeze-thaw cycles are preferable. 27 However, the intralesional cryosurgery technique is relatively much more powerful than contact or spray cryosurgery and thus leads to the death of BCC cells in a single freeze-thaw session.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the long duration of freezing enhances the biochemical changes and the growth of ice crystals, increasing the rate of cell death. 26 It has been reported that power of up to [35][36][37][38][39][40] W is required to destroy cancerous cells and that two freeze-thaw cycles are preferable. 27 However, the intralesional cryosurgery technique is relatively much more powerful than contact or spray cryosurgery and thus leads to the death of BCC cells in a single freeze-thaw session.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,10,11 From practical point of view, it has been observed that any procedure should be followed by IL steroids for several years, otherwise the procedure will be ineffective or even harmful. Strategy for therapy should be effective, with rapid result, practical to the patient and to the physician (can be performed as outpatient procedure), not expensive, and associated with restoration of maximum of normal texture and coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Eine weitere Arbeitsgruppe aus der Universität Aachen hat eine Zunahme der Effektivität durch die Kombination von IC und Silikonpflaster überprüft [17], [18]. Eine französische [8] und eine ägyptische [19] Arbeitsgruppe haben größere Patientenzahlen vorgelegt, die die von Har-Shai et al [12] berichteten Ergebnisse bestätigten.…”
Section: Die Publizierten Ergebnisseunclassified
“…Die posttherapeutische Anwendung von Silikongel und Silikondruckpflaster [17], [18] bzw. die Kombination mit der Injektion von intraläsionalen Steroiden können bei größeren Keloiden am Körper sinnvolle Kombinationen darstellen.…”
Section: Praktische Handhabungunclassified
See 1 more Smart Citation